Regionalism and the Agenda 2030 : inequality and decent work in Mexico - Mariano, Karina Lilia Pasquariello (2023)
The present study analyzes the limits of regionalism in achieving SDG 8, with a focus on the Mexican reality. It is based on the hypothesis that the role of the national government is decisive for incorporation of the Agenda 2030 in cases of regionalism based on an intergovernmental dynamic. We argue that NAFTA had a limited impact on improving working conditions in Mexico, as it only affected export-oriented regions and sectors. Since 2019 there has been an increase in the minimum wage, which can be explained not only by enforcing the USMCA, but also by a compatibility between internal and external agendas. Therefore, the case of Mexico allows us to affirm that the national government was decisive for the incorporation of the Agenda 2030 in the context of intergovernmental agreements.